Leverage as a Driver for Investment, Dividends, and the Impact on the Value of Real Estate Companies in Indonesia - Dwiatmanto Dwiatmanto; Suhadak Suhadak; Mochamad Dzulkirom AR; Siti Ragil Handayani (Wacana Journal of Social and Humanity Studies, 2020)
Based on the description of the background, the purpose of this study is to examine and explain the effect of leverage on the value of real estate companies listed on the Stock Exchange in Indonesia, with investment and dividend as mediators. This study is explanatory research. Explanatory is research conducted to explain the influence of variables through testing hypotheses. The population in this study is all real estate companies listed on the Indonesia Stock Exchange. The total population was as many as 44 companies. This study used four variables, which consisted of one exogenous variable and three endogenous variables. The categorized variables in exogenous variables are leverage (X) and as endogenous variables (Y) are (a) investment [Y1], (b) dividends [Y2], and (c) the company value [Y3]. The analytical method used is Generalized Structural Component Analysis (GSCA). The results of this study indicate that high dividend payments will cause a decrease in the value of the company. Several arguments can explain this. First, the market considers that at present the condition of the company has the opportunity to grow, so the company should focus on funding investment activities. Besides, also, with intense competition in the real estate sector, companies to be able to survive in the industry must have product innovations. The dividend payments are considered inappropriate by the market. The consequence of dividend payments is that companies will use high amounts of leverage. This is reinforced by the results of this study finding an indication of the use of high leverage will cause an increase in dividend payments.